Inovasi Pemasaran Aksesoris Sepeda Motor dengan Augmented Reality - Fatimah, Dini Destiani Siti; Rahayu, Raden Erwin Gunadhi; Habib, Reza Hasnan (Jurnal Algoritma, 2024)
Technological advances nowadays continue to increase rapidly, where shops or entrepreneurs who run their business using technology will provide advantages in doing business. Meanwhile, shops that do not have information technology in business will easily be overtaken by other shops, such as the Pitbox shop where sales have decreased due to the lack of technology in marketing products, making it difficult to reach potential customers and the lack of information is not conveyed to consumers. . This research aims to develop a website-based application that uses Augmented Reality (AR) technology to assist Pitbox shops in marketing motorbike accessory products. The main objective is to provide marketing media that can convey complete information about motorbike accessory products to consumers. The method used in this research is the Multimedia Development Life Cycle (MDLC), which consists of six stages, namely concept, design, material collecting, assembly, testing, and distribution. Augmented Reality technology is used to integrate AR features into the website applications being developed. The results of this research show that this application allows users to view motorbike accessories in real-time, provides complete information about the product, and improves consumer experience in selecting and purchasing motorbike accessory products.